-a(a-1)=0

Simple and best practice solution for -a(a-1)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -a(a-1)=0 equation:


Simplifying
-1a(a + -1) = 0

Reorder the terms:
-1a(-1 + a) = 0
(-1 * -1a + a * -1a) = 0
(1a + -1a2) = 0

Solving
1a + -1a2 = 0

Solving for variable 'a'.

Factor out the Greatest Common Factor (GCF), 'a'.
a(1 + -1a) = 0

Subproblem 1

Set the factor 'a' equal to zero and attempt to solve: Simplifying a = 0 Solving a = 0 Move all terms containing a to the left, all other terms to the right. Simplifying a = 0

Subproblem 2

Set the factor '(1 + -1a)' equal to zero and attempt to solve: Simplifying 1 + -1a = 0 Solving 1 + -1a = 0 Move all terms containing a to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1a = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1a = 0 + -1 -1a = 0 + -1 Combine like terms: 0 + -1 = -1 -1a = -1 Divide each side by '-1'. a = 1 Simplifying a = 1

Solution

a = {0, 1}

See similar equations:

| 10x-5=3y | | X+20x=180 | | 73=4n-7 | | 4(d-3)=-8 | | 2(6+s)+s-10+s=100 | | 2.5x(x+2)+4.5x=1.5(x-4) | | 3x+x-3=25 | | 0.2(n-5)=0.3n+6-4+0.1n | | -.55(x+2)=4.4 | | -8=(3-d)4 | | -2x+4y=-40 | | 1600=p(1+0.06) | | 5m-15-20m+5= | | (3x+6)(2x-12)(x+8)=0 | | -4y-2x=-8 | | -1.5x+y=320 | | 6f-13=24f-11 | | 6f-13=24f | | 1.4x+2y=800 | | 5*x-9+2*x+3=90 | | -4(x-2)+6x-15-x(4-3)=14-3(x+2)+7x-4 | | 0=-16 | | 380=2(w)(w+20) | | 5*4-9+2*4+3= | | 11+10=-8 | | 9+.75x=.875x-10 | | 5(4-3c)-6(2c+1)= | | 3t-2=t+10 | | 5(3)+x=21 | | 20x+345=51x+651 | | b=v*4-9 | | 6x-y-11=0 |

Equations solver categories